Kebertahanan Kosa Kata Tanaman Obat Tradisional dalam Lontar Taru Pramana di Desa Padangaji, Kecamatan Selat, Karangasem - I Kadek Widiantana (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
Lontar Taru pramana is one of the healing lontars. The existence of medicinal plants contained in the lontar, along with the times, is increasingly being abandoned. This also has an impact on the survival of the vocabulary of medicinal plants. Therefore, it is necessary to study the durability of the vocabulary. Based on the results of interviews conducted, the vocabulary of traditional medicinal plants in lontar taru pramana in Padangaji Village still survives. Of the 156 traditional medicinal plants listed in the lontar taru pramana text, 102 types of plants are known by the Padangaji community, but the persistence of the use of traditional medicinal plants in lontar taru pramana in Padangaji Village has not survived. This is because of the 156 types of medicinal plants found in lontar taru pramana, only 40 plants are known to be used by the Padangaji community or only 25%. The survival of the vocabulary of traditional medicinal plants in the Taru pramana lontar manuscript is not closely related to the persistence of the use of traditional medicinal plants in the village.